Changes in the Architectural Function of the Bolon House of the Toba Batak Ethnic Group from Social Function to Tourism Object - Alpiani Lubis; Immanuel Silaban; Eka Silviana Siregar; Doan Yohannes Manullang; Anggun Yuni Sarah Saragih (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to uncover changes in the social function of the Bolon House, the factors causing the changes, and their impact on the meaning and cultural values of the Toba Batak people. This study uses a descriptive qualitative approach with document-based analysis (documentary research). This approach was chosen because the study focuses on literature reviews and secondary data relevant to the changes in the function of the Bolon House, without conducting direct observations in the field. Data sources in this study consist of primary and secondary data, namely books, scientific articles, undergraduate theses, dissertations, and academic journals on Toba Batak architecture, as well as cultural tourism, as well as documentary data, namely digital archives, reports from local governments/tourism offices, and policy documents related to cultural preservation and tourism development. Data analysis was carried out through data reduction stages, sorting information from literature and documents relevant to the topic of changes in the function of the Bolon House. Categorization groups the data into themes: the traditional social function of the Bolon House, factors of change, implications for tourism, and cultural preservation. Although the change in function has the potential to reduce its sacred and social value, the existence of the Bolon House in the tourism sector also opens up opportunities for preservation, promotion of cultural identity, and empowerment of the local economy. Thus, this transformation needs to be managed wisely so that the Bolon House continues to function as a traditional architectural heritage that has sustainable social, cultural, and economic significance.